PEMBELAJARAN BERBASIS PROYEK PADA MATA KULIAH MEDIA PEMBELAJARAN DALAM PERANCANGAN MEDIA BELAJAR DI SEKOLAH DASAR - Siti Quratul Ain; Elpri Darta Putra; Eva Astuti Mulyani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to explain project-based learning activities on instructional media courses for the design of learning media at elementary schools. This study also aimed to determine the students’ perceptions towards project-based learning in instructional media courses.  This study was a quantitative descriptive study using literature study and surveys.  One of learning activities in media course which used project-based learning model was designing visual, audio-visual, and multimedia learning media. The stages in designing the learning media were started from analyzing basic competencies in one subject, making a learning media framework, creating the design results, and finally presenting how to use the learning media as well as publishing to Google Classroom. The results revealed that students' perceptions towards project-based learning in learning media courses based on each indicator were as follow. The percentage for the indicator of student and lecturer interactions was 82.53% (good); for the indicator of students’ learning interests was 80.66% (good); for the indicator of competency in understanding teaching materials was 88.53% (good); for the indicator of competency to think critically, effectively, and efficiently was 88.66% (good); for the indicator of time management competence was 80.26 (good); for the indicator of students’ learning outcomes was 88.40% (good), and for the appropriateness of project-based learning application with subject characteristics was 91.20  % (very good).